Dispute Resolution on Agreements Fiduciary in Tort Settlement (Case Study in PT. Adira Multi Dynamics Finance Tbk, Denpasar II Branch) - A. A. Sagung Ngurah Indradewi; I Wayan Nik Mudarana (Fakultas Hukum, Universitas Warmadewa, 2023)
Phenomena that often occur in decision making or policies which of course are based on applicable regulations or agreements are confiscation or taking guarantees or otherwise the submission of guarantees by the debtor due to a default or unable to carry out their obligations properly. As many have done, it can be seen from the data in PT. Adira Dinamika Multi Finance Tbk, Denpasar II Branch. Based on this background, the formulation of the problem found is how is the form of dispute resolution regarding the fiduciary agreement in the settlement of default at PT. Adira Dinamika Multi Finance Tbk, Denpasar II Branch, and What are the obstacles faced in the execution of fiduciary guarantees at PT. Adira Dinamika Multi Finance Tbk, Denpasar II Branch?This type of research uses empirical legal research methods. The nature of this research is descriptive. Data and Data Sources used are primary data and secondary data. Data collection techniques used are observations, interviews and documentation. After the data is collected, it is analyzed using qualitative analysis methods. The conclusion of this research is the form of dispute resolution at PT. Adira Dinamika Multi Finance Tbk, Denpasar II Branch is divided into 2 stages, namely non-litigation efforts and litigation efforts. Constraints faced in the execution of fiduciary collateral goods at PT. Adira Dinamika Multi Finance Tbk, Denpasar II Branch is in executing the goods that have been transferred by the debtor of the goods. but as a result of the acknowledgment of the droit de suite principle that fiduciary security rights follow the object in the hands of whoever the object is.